The Field of Free Time as Tertiary Agency of Socialisation - Nagy Ádám; Kerpel-Fronius Balázs (Sciendo, 2024)
Introduction: The authors examine the agencies of socialisation and attempt to reveal a pattern among these agents. They differentiate social elements and agencies of socialisation, and they endow the latter with three conditions: the requirements of scope, time and intensity and specific set of rules.